Gonadotropin inhibitory hormone (GnIH) prevents the ‘priming’ effect of estradiol-17β - Ika Puspita Sari; Jessica Jacobi; Alexandra Rao; Iain Clarke (Indonesian Journal of Pharmacy, 2011)
GnIH  inhibits  GnRH-stimulated  gonadotropin  secretion  in  the  sheep  by action on the pituitary gonadotropes. Estradiol-17β(E2) also acts at the level of the  pituitary  gonadotrope  to  exert  negative  and  positive  feedback  effects  on gonadotropin secretion. The positive effect facilitates the estrogen-induced surge in  gonadotropin  releasing  hormone  (GnRH)  and  LH.  This  study  was  undertaken to  determine  whether  this  ‘priming’  effect  of  E2  is  prevented  by  GnIH.  Cultured pituitary  cells  were  treated  with  GnRH  or  vehicle  every  4  h  for  24  h  with  and without  GnIH  and  E2 treatment.  GnRH  stimulated  (LH)  and  follicle  stimulating hormone  (FSH)  secretion  was  increased  by  E2 treatment.  The  effect  of  E2  was overcomes  by  the  inhibitory  effect  of  GnIH.  We  conclude  that  GnIH  may counteract the priming effect of E2 on pituitary gonadotropes.Key words:Gonadotropin, gonadotrope, gonadotropin inhibitoryhormone, estradiol